Hospital Patient Loyalty: In terms of Brand Image, Service Quality, Patient Satisfaction, and Trust - Puguh Ika Listyorini; Warsi Maryati; Sylvia Anjani (LPPM Universitas Duta Bangsa Surakarta, 2021)
The success of a hospital if it has loyal patients. Patient loyalty depends on the brand image of the hospital, the quality of service to patients, patient satisfaction, and patient trust in the hospital. This study aims to determine whether there is a relationship between brand image, service quality, satisfaction, and patient trust on patient loyalty. This type of research is analytic observational research with a cross-sectional approach. Samples were taken by accidental sampling with a total of 156 patients. The results showed that there was a relationship between brand image, service quality, satisfaction, and patient trust on patient loyalty.